STRATEGI KOMUNIKASI PEMASARAN DALAM MENGEMBANGKAN PARIWISATA DI DANAU TOBA: STUDI KASUS BADAN KOORDINASI PELESTARIAN EKOSISTEM KAWASAN DANAU TOBA (BKPEKDT) - Ginting, Teria S (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2023)
This research aims to determine how to communicate and examine the effectiveness of marketing communication strategies used by BKPEKDT for tourism development on Lake Toba. The research method used is qualitative with the type of case study research by selecting informants who work actively in BKPEKDT. This study uses the constructivism paradigm. The strategy used is included in the promotion mix, one of which is by holding an event. The results of this study found that the marketing methods used were still simple and needed to maximize the existing marketing concepts. More attractive and interactive strategies and promotions are required.